Effects of climate shocks on human fertility in Indonesia: a retrospective, panel analysis of household survey and climate data - Samuel Sellers, PhD; Clark Gray, PhD (The Lancet Planetary Health, 2018)
Background: Climate change is likely to induce a large range of household-level responses, including changes in human fertility behaviours and outcomes. These responses might have important implications for human and economic development, women's empowerment, and environmental sustainability. However, to date, few studies have explored the associations between climate change and fertility intentions, family planning use, and births. Methods: Drawing on the literature linking climate variability to rice production in Indonesia, we used large-scale, longitudinal household survey data and high-resolution climate data to explore changes in childbearing preferences, family planning use, and births after community-level climate anomalies (timing of monsoon onset and temperature) in Indonesia between 1993 and 2015. Analyses were done with a series of fixed-effects, logistic regression models. We also assessed parallel shifts in household wellbeing, as measured by expenditure on rice, food, and non-food products. Findings: We found that, in the short term (climate anomalies occurring 1–12 months before surveys), fertility desires increased and family planning use declined in response to delays in monsoon onset, particularly in wealthier populations. Delays in monsoon onset were also associated with substantially reduced expenditure on food and non-food products among households without farm businesses and high levels of education. In the medium term (climate anomalies occurring 1–60 months before surveys), fertility desires declined and family planning use increased in response to high temperatures, particularly in poorer populations. Interpretation: These results suggest that fertility desires, family planning use, and births are affected by climate shocks. Provision of high-quality family planning services can serve as an important climate change adaptation tool for vulnerable populations. Funding: None.